AstroSat UVIT Survey of M31: New Compact Source Catalog - Denis Leahy; Sujith Ranasinghe; Saptadwipa Mitra; Kripansh Rawal (The Astrophysical Journal Supplement Series)
An ultraviolet survey of M31 was carried out during 2017–2023 with the UltraViolet Imaging Telescope (UVIT) instrument on board the AstroSat Observatory. Here we present far- and near-ultraviolet (FUV and NUV) observations from the M31 UVIT survey, which covers a sky area of ≃3 $\mathop{.}\limits^{\unicode{x000b0}}$ 5 × 1 $\mathop{.}\limits^{\unicode{x000b0}}$ 3 with a spatial resolution of ≃1″. The observations included six filter bands in the wavelength range of 120–280 nm. Including the six bands, ≃115,000 sources with signal-to-noise ratio (S/N) ≥ 3 (≃95,000 sources with S/N ≥ 5) were detected at FUV or NUV wavelengths, with the largest set of detections (≃54,000 sources) in the FUV 150 nm band (F148W filter). This is considerably more than for the first version of the M31 source catalog (published in 2020), in part due to additional observations of M31 by UVIT and in part due to improved data processing. The magnitude ( m _AB ) at which incompleteness sets in is ≃23.0 in the F148W band, with the other bands somewhat less sensitive, with least sensitive band (in m _AB units) N279N with incompleteness for sources fainter than ≃20.3). The faintest sources detectable in F148W have m _AB  ≃ 25.4, with other bands having higher minimum detectable brightness, and with N279N having a minimum detectable limit of m _AB  ≃ 22.1. The product of this work is the new M31 UVIT compact-source catalog, containing positions, fluxes, magnitudes, and S/N for the sources.